Molecular mechanisms of Cys-loop ion channel receptor modulation by ivermectin - Lynagh, Timothy; Lynch, Joe (Frontiers in Molecular Neuroscience, 2012)
Ivermectin is an anthelmintic drug that works by inhibiting neuronal activity and muscular contractility in arthropods and nematodes. It works by activating glutamate-gated chloride channels (GluClRs) at nanomolar concentrations. These receptors, found exclusively in invertebrates, belong to the pentameric Cys-loop receptor family of ligand-gated ion channels (LGICs). Higher (micromolar) concentrations of ivermectin also activate or modulate vertebrate Cys-loop receptors, including the excitatory nicotinic and the inhibitory GABA type-A and glycine receptors (GlyRs). An X-ray crystal structure of ivermectin complexed with the C. elegans α GluClR demonstrated that ivermectin binds to the transmembrane domain in a cleft at the interface of adjacent subunits. It also identified three hydrogen bonds thought to attach ivermectin to its site. Site-directed mutagenesis and voltage-clamp electrophysiology have also been employed to probe the binding site for ivermectin in α1 GlyRs. These have raised doubts as to whether the hydrogen bonds are essential for high ivermectin potency. Due to its lipophilic nature, it is likely that ivermectin accumulates in the membrane and binds reversibly (i.e., weakly) to its site. Several lines of evidence suggest that ivermectin opens the channel pore via a structural change distinct from that induced by the neurotransmitter agonist. Conformational changes occurring at locations distant from the pore can be probed using voltage-clamp fluorometry (VCF), a technique which involves quantitating agonist-induced fluorescence changes from environmentally sensitive fluorophores covalently attached to receptor domains of interest. This technique has demonstrated that ivermectin induces a global conformational change that propagates from the transmembrane domain to the neurotransmitter binding site, thus suggesting a mechanism by which ivermectin potentiates neurotransmitter-gated currents. Together, this information provides new insights into the mechanisms of action of this important drug.